2018
DOI: 10.3390/molecules23010056
|View full text |Cite
|
Sign up to set email alerts
|

Improved Physicochemical Properties of Yogurt Fortified with Fish Oil/γ-Oryzanol by Nanoemulsion Technology

Abstract: Fish oil has several dietary benefits, but its application in food formulations is limited because of its poor water-solubility, easy oxidation and strong odor. The purposes of this study were to produce a fish oil/γ-oryzanol nanoemulsion and to evaluate the effect of adding this nanoemulsion on the physicochemical and sensory characteristics of yogurts. Adding fish oil/γ-oryzanol nanoemulsion resulted in a significant reduction in the acidity and syneresis of yogurt. Yogurt with the nanoemulsion had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 27 publications
2
41
1
2
Order By: Relevance
“…The addition of the NE did not influence the melting and crystallization behavior of fortified yogurt mixes. Sensory evaluation data showed yogurt fortified with fish oil/γ-oryzanol NE had closer scores of sensory attributes to plain yogurt than yogurt fortified with fish oil and γoryzanol (Zhong et al, 2018). These studies showed that yogurt could be fortified with fish oil/γ-oryzanol NE to create a potential product with considerable dietary benefits due to the high availability of these poor water-soluble components.…”
Section: Applications Of Nanoemulsionsmentioning
confidence: 83%
See 2 more Smart Citations
“…The addition of the NE did not influence the melting and crystallization behavior of fortified yogurt mixes. Sensory evaluation data showed yogurt fortified with fish oil/γ-oryzanol NE had closer scores of sensory attributes to plain yogurt than yogurt fortified with fish oil and γoryzanol (Zhong et al, 2018). These studies showed that yogurt could be fortified with fish oil/γ-oryzanol NE to create a potential product with considerable dietary benefits due to the high availability of these poor water-soluble components.…”
Section: Applications Of Nanoemulsionsmentioning
confidence: 83%
“…However, its exploitation in food products is limited due to its poor water solubility, natural oxidation, and strong odor. Zhong, Yang, Cao, Liu, and Qin (2018) studied the adding of fish oil/γ-oryzanol NE on the physicochemical and sensorial properties of yogurts. Adding NE loaded with fish oil and γ-oryzanol into yogurt resulted in a critical reduction in acidity, syneresis, and peroxide value (Zhong et al, 2018).…”
Section: Applications Of Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish oil extracted from fish wastes is an excellent source of many unsaturated fatty acids, including long chain omega-3 cis-5,8,11,15,17-eicosapentaenoic acid (EPA) and cis-4,7,10,13,16,19-docosahexaenoic acid (DHA) [ 137 ]. However, its application in food formulations fortified in omega-3 is limited because of its easy oxidation and strong odor [ 41 ]. Successful attempts to develop yogurts containing omega-3 that had sensory attributes similar to plain yogurt were obtained by encapsulating fish oil in nano-liposomes [ 40 ], and adding a fish oil/γ-oryzanol nanoemulsion to yogurt [ 41 ].…”
Section: Approaches In the Application Of Food Byproducts In The Dmentioning
confidence: 99%
“…Pike and Jackson (2010) stated that fish oil could be applied directly to food products to cover the fishy smell. Some studies have used fish oil as a food additive by adding it to yogurt (Zhong et al, 2018), butter (Subroto et al, 2018) and bakery products such as cakes (Santhanam et al, 2015). Fish oil mixed with vegetable oil can enrich omega-3 fatty acids, like virgin coconut oil (Apraku et al, 2017), linseed oil and palm oil (Monge-Ortiz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%